Chromoendoscopy with a Standard-Resolution Colonoscope for Evaluation of Rectal Aberrant Crypt Foci - Kowalczyk, Marek (PLoS One, 2016)
Colorectal cancer (CRC) is the second most common cause of death worldwide. According to the theory by Vogelstein, colorectal carcinogenesis involves a series of successive changes in the normal colonic mucosa, starting with excessive proliferation and focal disorders of intestinal crypts, followed by adenoma and its subsequent malignant transformation. The first identifiable changes in CRC carcinogenesis are aberrant crypt foci (ACF). ACF are invisible during routine colonoscopy yet are well identifiable in chromoendoscopy using methylene blue or indigo carmine. High-resolution colonoscopes are used for assessment of ACF. The aim of the present study was to evaluate the usefulness of standard-resolution colonoscopy for identification of rectal ACF. The following parameters were evaluated: duration of chromoendoscopy of a given rectal segment, type of ACF, sensitivity and specificity of endoscopy combined with histopathological evaluation. The mean duration of colonoscopy and chromoendoscopy was 26.8 min. In the study population, typical ACF were found in 73 patients (p = 0.489), hyperplastic ACF in 49 (p = 0.328), and dysplastic ACF in 16 patients (p = 0.107). Mixed ACF were observed in 11 individuals (p = 0.073). The sensitivity of the method was found to be 0.96 whereas its specificity 0.99. Identification of rectal ACF using standard-resolution colonoscopy combined with rectal mucosa staining with 0.25% methylene blue is characterised by high sensitivity and specificity.